5 - Institutionalizing Gender-Based Violence Within African Democracies: A Comparative Analysis of South Africa And Botswana - Kang, Kyunghee; Kim, Taekyoon (Africa Development, 2024)
Even though international legislation recognises the eradication of gender- based violence as a crucial target for the promotion of human rights and the achievement of the sustainable development of the world, violence against women has received little intellectual attention and scholarly intervention from academia. In the African region, where diverse sociocultural and institutional gender discriminative factors often mean unequal power relations between women and men, the prevalence of gender-based violence is particularly critical. This article examines the institutional implications of violence against women by comparing South Africa and Botswana, two countries that adopted democratic systems after gaining independence from the United Kingdom. It highlights the importance of the Constitutions of both countries and the representation of woman in politics. The divergence between the two states’ legal and political approaches to gender equality and human rights underscores the role of gender-specific institutions in the prevalence of violence against women. This article also uncovers the limitations of existing strategies and proposes a better understanding of inequality within gender relations and its reflection within the frame of institutions to find a way to resolve violence against women and achieve gender justice.